Taurine ameliorates neuropathy via regulating NF-?B and Nrf2/HO-1 signaling cascades in diabetic rats - Agca, Can Ali; Tuzcu, Mehmet; Hayirli, Armagan; Şahin, Kazım (Pergamon-Elsevier Science Ltd, 2014)
Diabetic neuropathy is one of common complications of diabetes mellitus. Hyperglycemia induced oxidative stress involves in the development of diabetic neuropathy, which could be reversed by supplementation of taurine, an endogenous antioxidant. This experiment was conducted to evaluate alterations in the expressions of transcription factors [nuclear factor kappa B (NF-kappa B), nuclear factor-E2-related factor-2 (Nrf2), and heme oxygenase 1 (HO-1)] and glucose transporters and glucose metabolism in the brain of diabetic rats. In a 2 x 2 factorially arranged groups, taurine (2%) or water was administered per orally to healthy and streptozotocin (STZ)-induced diabetic rats (n = 10 per group) for 8 weeks. Diabetes was associated with weight loss, hyperglycemia, and oxidative stress as reflected by increased serum malondialdehyde (MDA) concentrations. Diabetic rat brains had increased the NF-kappa B expression and decreased the Nrf2, HO-1, GLUT1,3 expressions as compared to healthy rat brains. Supplemental taurine did not alter body weight and blood glucose concentration, but partially reduced serum MDA concentration in the diabetic rats. Taurine also partially alleviated neuroinflammation as reflected by suppressed the NF-kappa B expression and enhanced the Nrf2, HO-1, GLUT1,3 expressions in the diabetic rats. In conclusion, taurine reduces the severity of oxidative stress through activating antioxidative defense signaling pathway in diabetic rat brain. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Diabetic neuropathy; Oxidative stress; Taurine; NF-kappa B; Nrf2; HO-1